Special report: Coronavirus puts youth sports on pause - Baker, K.; Tracy, J. (2020)
When you hear "youth sports," colorful images of orange slices and vivid memories of pizza parties might fill your head. Perhaps then your mind shifts to some of the recent trends: skyrocketing costs, participation declines, the rise of specialization and the world of pay-to-play leagues and mega-complexes.